Analysis of Data Warehouse for Transactional Analysis Methods Online Analytical Processing (OLAP) at Company XYZ Silver - Widiadnyana, Putu; Maricar, M. Azman; Arnawan, I Nyoman; Ariyani, Sri (International Journal of Engineering and Emerging Technology, 2017)
Utilization of information technology is a necessity in looking at opportunities available for decision making by the management. With the ability of information technology to analyze existing used the data into useful information for a company. OLAP is Able to Overcome problems in the data processing mechanisms guided to know various information from different angles. By utilizing transactional analysis, then we know the reaction of customers in choosing the products that we will market. The result of Web-based sales has Decreased for the Gianyar and Denpasar regions but has Increased for the Ubud and online areas so as to give a benefit in terms of production costs. With the training for a sales increase of sales can evenly across locations and need input from customers related to minimize returns.